Perioperative Period is a Critical Gap for Minimal Residual Cancer Cells Progression and Therapy: Biological and Molecular Based Evidences - Tawfik Amin, Anwar; Shiraishi, Norio; Kitano, Seigo (Journal of Hematology and Oncology Research, 2018)
Although surgery is the main treatment for solid tumors, it could enhance the growth and metastasis of minimal residual cancer. In this review article we have discussed the perioperative changes in cancer cells and surrounding environment as well as the alterations in the immune system. Several trials are ongoing to develop new diagnostic and therapeutic options for minimal residual cancer after surgery.
Keywords: surgical stress; pain and cancer recurrence; surgery induced immune suppression; tumor growth